Mosaic expression of a tyrosinase fusion gene in albino mice yields a heritable striped coat color pattern in transgenic homozygotes. - Mintz, B (1991)
Genetically albino mouse eggs were injected with an inducible transgene comprising the wild-type tyrosinase (monophenol, L-dopa: oxygen oxidoreductase, EC 1.14.18.1) cDNA and the metallothionein gene promoter in the expectation that the transgene would be expressed to different extents in the various developing pigment cell clones of at least some individuals, thereby leading to patterned coats. This proved to be the case. Five transgenic mice had lightly pigmented patterns of transverse stripes visualizing melanoblast proliferation and migration dorsoventrally on each side. Similar patterns have been seen in genetically mosaic mouse models produced from conjoined blastomeres of different color genotypes and in many naturally patterned genotypes of mice. Four of the transgenics had heritable patterns and autosomal transgene integration. Their homozygous descendants were darker than hemizygotes and transmitted the basic pattern through many generations. Eyes were also pigmented, with clonal patches of melanized cells in the retinal pigment epithelium. The skin was dark due to many pigmented dermal melanocytes, whereas relatively few were in the hair follicles. This "inversion" is attributable to precocious maturation and migratory arrest of many melanoblasts during passage through the dermis en route to the hair bulbs. Patterning in these mice is considered in light of the view, previously proposed, that phenotypically different clones, or phenoclones, may exist in virtually all mammalian cell types and that many genes may be associated with cis-acting control regions causing variations in their expression that are mitotically perpetuated. We point out that mosaic expression has many implications for development as well as neoplasia. In the latter case, the potential for tumor susceptibility may be affected by clonal variation without further gene mutations or deletions. Thus, mice with variegating transgenes can provide molecular access to gene control mechanisms and to their consequences in development and disease.